EDUCATIONAL SOFTWARE IN TEACHING - Irina F. Kisselman; Madina G. Yudina (Moscow Polytechnic University, 2022)
This paper stands as an argument for employing educational software in teaching and evaluating skills and knowledge in higher education. The authors' main goal is to pinpoint and focus on strategies of teaching through the use of modern means, namely educational software.